A comparison of peer relations and social skills of children aged between 5 and 6 with and without divorced parents - (:unkn) unknown (SILA SCIENCE, 2012)
The purpose of this study is to compare the social skill levels and peer relations of 5-6 year olds with divorced parents to 5-6 year olds whose parents are together. 70 children aged between 5 and 6 participated in the study. 35 of the children's parents were divorced. The remaining 35 children's parents were together. A personal information form, the Child Behaviour Scale, and the Social Skills Assessment Scale were used to gather data. The data collecting instruments were completed by preschool teachers. According to study results, the divorce variable, in general, has an effect on the social skills and peer relations of children aged between 5 and 6. While children with divorced parents had a lower level of prosocial behaviour and social skill in comparison to their peers, whose parents are together, their level of asocial behaviour, exclusion, and fear-anxiety was higher in comparison to their peers, whose parents are together. There was no difference in the level of hyperactivity directed at peers among both groups.
Keywords: Divorce; Peer relations; Social skills; Preschool period; EARLY-CHILDHOOD; CANDIDATES; CONFLICT